2018
DOI: 10.3390/antiox7090120
|View full text |Cite
|
Sign up to set email alerts
|

Bark of Passiflora edulis Treatment Stimulates Antioxidant Capacity, and Reduces Dyslipidemia and Body Fat in db/db Mice

Abstract: Obesity is considered an important risk factor for several disorders, such as diabetes mellitus, systemic arterial hypertension, dyslipidemia, and atherosclerosis, which are associated with inflammation and oxidative stress as a trigger factor. Passiflora edulis contains important bioactive compounds, such as phenolics, carotenoids, vitamin C, and polyamines in pulp, leaves, seeds, and bark. Aim: To evaluate the effect of bark of Passiflora edulis (BPe) on body composition, and metabolic and oxidative stress p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
0
26
0
3
Order By: Relevance
“…These antioxidant properties were linked with flavonoids determined in the ethanol extract (mainly vicenin, vitexin, isovitexin, orientin). In comparison, recently Panelli et al [54] exerted that extract from the fruit bark (exocarpium and mesocarpium) of P. edulis increased the antioxidant capacity in vivo in plasma, kidney, liver, adipose tissue of db/db mice by inhibition of 4,4-difluoro-5-(4-phenyl-1,3-butadienyl)-4-bora-3a,4a-diaza-s-indacene-3-undecanoic acid and also reduced the lipid oxidation in kidney and liver using method with malondialdehyde. In vitro test showed additionally that this extract inhibited DPPH with value 1.1 µM equiv.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…These antioxidant properties were linked with flavonoids determined in the ethanol extract (mainly vicenin, vitexin, isovitexin, orientin). In comparison, recently Panelli et al [54] exerted that extract from the fruit bark (exocarpium and mesocarpium) of P. edulis increased the antioxidant capacity in vivo in plasma, kidney, liver, adipose tissue of db/db mice by inhibition of 4,4-difluoro-5-(4-phenyl-1,3-butadienyl)-4-bora-3a,4a-diaza-s-indacene-3-undecanoic acid and also reduced the lipid oxidation in kidney and liver using method with malondialdehyde. In vitro test showed additionally that this extract inhibited DPPH with value 1.1 µM equiv.…”
Section: Resultsmentioning
confidence: 90%
“…Earlier studies showed that various extracts from leaves of many Passiflora species contain these groups of phytochemicals and they may have contributed to their excellent radical scavenging ability. Most studies were carried out for extracts from fruits of P. edulis [48,[51][52][53][54][55][56][57][58][59][60]. To the best of our knowledge, any studies evaluating the antioxidant activity of the methanol extract of P. caerulea leaves have been conducted so far.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, at the age of 14 days, the TG level in the plasma of sucking piglets was reduced, but the levels of ALT,AKP,IL-1β,IL-6 and IL-10 in the plasma of sucking piglets were increased in the FD group. ALT and AKP is positively correlated with the degree of abnormal liver tissue [20][21][22]. IL-10 is an anti-in ammatory regulatory cytokine, which could induce antibody production and improve anti-in ammatory ability [23].…”
Section: Discussionmentioning
confidence: 99%
“…Paralelo a isso, há grande capacidade de aproveitamento, desconhecidas por muitos, onde esses resíduos passam a ser matéria prima para elaboração de vários produtos alimentícios como doces, geleias, bolos, barras de cereal e óleos (SILVA et al, 2015;SANTOS, 2017;MAIA, 2018). Já a casca de maracujá, composto de flavedo e albedo (parte branca) é constituída por carboidratos, proteínas e é rica em fibras, estas de suma importância para a prevenção de doenças cardiovasculares (PANELLI et al, 2018;QUEIROZ, 2018;SATIJA;HU, 2018). Na casca destaca-se a presença da pectina que é uma fibra solúvel que além de dar sensação de saciedade, facilita o trânsito intestinal e auxilia na redução do índice glicêmico, ademais, é fonte de niacina (vitamina B3), ferro, cálcio e fósforo (MORENO, 2015;MÜLLER;CANFORA;BLAAK, 2018;SILVA, 2018;DE ALBUQUERQUE et al, 2019).…”
Section: Resíduos Do Maracujáunclassified